A protected group-containing sulfonated hydrocarbon polymer, a synthetic method and application in low-temperature proton exchange membrane fuel cells

CN117586485BActive Publication Date: 2026-10-09INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311564859.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-22
Publication Date
2026-10-09
Estimated Expiration
2043-11-22

AI Technical Summary

Technical Problem

Liu等设计合成一系列含磺酸基团的聚醚酮(PEK-SPx),通过引入多个磺酸基团来提高电池性能,其中PEK-SP20膜的表现出高的质子传导能力,但是膜的溶胀较大,导致差的尺寸稳定性及机械性能降低(Journal ofPower Sources,482(2021),228982)

Benefits of technology

[0031] (1) The polymer electrolyte of the present invention is a sulfonated hydrocarbon high molecular weight copolymer containing different protecting groups. The present invention uses biphenyl and indigo in different proportions and indigo monomers containing different protecting groups for acid-catalyzed polymerization, followed by sulfonation with concentrated sulfuric acid to obtain an IEC-controllable sulfonated polymer electrolyte. This polymer exhibits controllable water absorption capacity, good dimensional stability, mechanical stability, and oxidative stability, and shows excellent performance as a proton exchange membrane and ionomer binder in low-temperature proton exchange membrane fuel cells;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117586485B_ABST
    Figure CN117586485B_ABST
Patent Text Reader

Abstract

The application discloses a sulfonated hydrocarbon polymer containing a protecting group, a synthesis method and application in a low-temperature proton exchange membrane fuel cell. The polymer electrolyte is a high-molecular-weight copolymer of an indigo monomer containing a certain amount of protecting groups and diphenyl, the main chain of which is a rigid hydrophobic aryl skeleton without ether bonds, and the active position of the indigo is suspended with a sulfonic acid group after sulfonation by 98% concentrated sulfuric acid. The sulfonated hydrocarbon polymer containing the protecting group can control the ion exchange capacity (IEC) of the polymer, change the water absorption capacity, thereby controlling the volume swelling and size stability of the proton exchange membrane and ionomer binder, and improving the mechanical strength of the polymer by changing the number and type of the protecting group. The obtained polymer is applied to the low-temperature proton exchange membrane fuel cell as the proton exchange membrane and the binder, and shows good initial performance and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a sulfonated polymer electrolyte with controlled ion exchange capacity (IEC) by introducing a protecting group, a synthesis method, and its application in cryogenic fuel cells. It belongs to the field of cryogenic fuel cell technology, and specifically relates to a sulfonated hydrocarbon polymer containing a protecting group, a synthesis method, and its application in cryogenic proton exchange membrane fuel cells. Background Technology

[0002] Low-temperature proton exchange membrane fuel cells (PEMFCs) are a novel type of power generation device that converts the chemical energy of fuel into electrical energy. Their high energy density, high energy conversion efficiency, and environmental friendliness make them one of the most promising clean energy sources. As core components of fuel cells, the proton exchange membrane and ionomer binder play crucial roles. The proton exchange membrane can conduct hydrogen... + Ions separate the cathode and anode; the ionomer binder of the catalyst layer affects the mass transfer performance and electrochemical reactivity of the catalyst layer by forming a three-phase interface between H2O, solid catalyst, and reactant gases. To date, perfluorosulfonic acid polymers, such as Nafion, are the most popular commercially available proton exchange membrane and ionomer binder due to their high proton conductivity, mechanical properties, and oxidative stability. However, Nafion's high cost, environmental pollution, gas leakage, and complex preparation process hinder its large-scale commercialization. To replace perfluoropolymers, various sulfonated polymers have been successfully synthesized, and their properties have been investigated.

[0003] To improve battery performance, proton exchange membranes with high ion exchange capacity (IEC) and ionomer binders are required. However, high IEC can lead to excessive water absorption and harmful volume expansion. Therefore, proper water management is crucial for achieving better performance in proton exchange membrane fuel cells. Liu et al. designed and synthesized a series of polyetherketones (PEK-SPx) containing sulfonic acid groups to improve battery performance by introducing multiple sulfonic acid groups. Among them, the PEK-SP20 membrane exhibited high proton conductivity, but the membrane swelled significantly, resulting in poor dimensional stability and reduced mechanical properties (Journal of Power Sources, 482(2021), 228982). Yang et al. grafted a certain number of long side-chain sulfonic acid groups onto the fluorene structure of the polymer backbone, but the synthetic route was complex and unsuitable for large-scale synthesis (Journal of Materials Chemistry A, 11(2023), 4547-4558). Ding et al. grafted long-chain sulfonic acid groups onto the -NH group of the polymer backbone indigo, but the precision was difficult to control (Journal of Membrane Science, 664(2022), 121045). Therefore, by copolymerizing indigo, indigo, and biphenyl with different proportions of protecting groups, the IEC of the sulfonated hydrocarbon copolymer can be controlled by the protecting groups, thereby obtaining a sulfonated polymer electrolyte with low swelling and high mechanical stability. Therefore, it is expected to become a proton exchange membrane, ionomer binder material, and applied to low-temperature proton exchange membrane fuel cells. This research has not been reported in the literature. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings and problems of existing technologies by proton exchange membranes (PEMs) which, while achieving high ion exchange capacity (IEC), suffer from issues such as high volume swelling and poor stability. This invention proposes a hydrocarbon polymer electrolyte (PEM and binder) containing protecting groups. By altering the number and type of protecting groups, the IEC of the polymer can be precisely controlled, changing its water absorption capacity and thus regulating the balance between proton transport capacity and size swelling, thereby improving the lifespan of PEM fuel cell devices. This invention provides a sulfonated hydrocarbon polymer containing protecting groups, its synthesis method, and its application in low-temperature PEM fuel cells. Specifically, this application refers to the use of a sulfonated hydrocarbon polymer containing protecting groups as both a membrane and a binder in low-temperature PEM fuel cells.

[0005] To achieve the above objectives, the present invention discloses the following technical content:

[0006] 1. The present invention discloses a series of sulfonated hydrocarbon polymer structures containing different protecting groups and different IECs, as shown in the following formula:

[0007]

[0008] Wherein, R3 is selected from F, Cl, Br, I, NO2, CH3 or CH3O, R1, R2 and R4 are each independently selected from H, F, Cl, Br, I, NO2 or CH3, n and (100-n) represent the polymerization ratio, and n is selected from an integer from 20 to 100 (e.g., n is 20, 30, 40, 45, 49, 50, 51, 52, 55, 60, 65, 70, 75, 80, 85, 9). The weight-average molecular weight of the polymer is between 5,000 and 800,000 (e.g., 5,000, 10,000, 15,000, 50,000, 100,000, 150,000, 200,000, 300,000, 400,000, 600,000, 700,000, or 800,000). Preferably, when R3 is selected from F, Cl, Br, I, NO2, CH3, or CH3O, R1 is H, R2 is H, and R4 is H. Optionally, when R3 is selected from F, Cl, Br, I, NO2, CH3 or CH3O, R1 is F, R2 is H and R4 is H; when R3 is selected from F, Cl, Br, I, NO2, CH3 or CH3O, R1 is H, R2 is F and R4 is H.

[0009] The method for synthesizing sulfonated hydrocarbon polymers as described above includes the following steps:

[0010] (1) At room temperature, the reaction raw materials indigo, indigo monomer with a protecting group, biphenyl, polar organic solvent and trifluoroacetic acid (TFA) are first mixed and stirred until uniform; under ice bath conditions, trifluoromethanesulfonic acid (TFSA) is added dropwise to the solution to initiate the polymerization reaction, and then the system is gradually heated to room temperature. The mixture is then poured into alcohol to obtain fibrous polymer. Excess acid in the solution is removed with alkaline solution, and then the system is washed multiple times with deionized water until neutral. The mixture is then filtered to obtain fibrous solid polymer, which is the polymer precursor with a protecting group.

[0011] (2) The polymer precursor and sulfonating agent are mixed to obtain a reaction solution with a solid content of 3-6 wt% (e.g., 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 4.7 wt%, 4.9 wt%, 5 wt%, 5.2 wt%, 5.4 wt%, 5.6 wt%, 5.8 wt%, or 6 wt%) and a reaction temperature of 20-60°C (e.g., 20°C, 30°C, 35°C, 40°C, 45°C, 47°C, 50°C, 52°C, 55°C, or 60°C). The reaction continues until the polymer dissolves in the sulfonating agent. The solution is then immersed in distilled water to obtain flocculent material. The flocculent material is washed several times with distilled water until the system is neutral. The filtered sulfonated polymer is then vacuum dried to obtain a sulfonated polymer with low IEC.

[0012] Further, in step (1), the indigo monomer containing the protecting group is 5-fluoroindigo, 5-chloroindigo, 5-bromoindigo, 5-iodoindigo, or 5-nitroindigo, etc. Preferably, the molar ratio of biphenyl:indigo:indigo monomer containing the protecting group is 10:(2-11):(9-0). More preferably, the molar ratio of biphenyl:indigo:indigo monomer containing the protecting group is 10:5.5:5.5, 10:7.7:3.3, or 10:9.9:1.1. For example, the molar ratio of biphenyl:indigo:indigo monomer with protecting group is 10:2.2:8.8, 10:3.3:7.7, 10:4.4:6.6, 10:5:6, 10:5.5:5.5, 10:6:5, 10:6.6:4.4, 10:7:4, 10:7.5:3.5, 10:8:3, 10:8.5:2.5, 10:9:2, 10:9.5:1.5, 10:10:1, or 10:10.5:0.5. Preferably, the ratio of biphenyl, polar organic solvent, trifluoroacetic acid, and trifluoromethanesulfonic acid is 10 mol: 1–4 mL: 1–4 mL: 5–10 mL.

[0013] Further, in step (1), the polar solvent is dichloromethane at room temperature. Under the ice bath conditions, the reaction system temperature is below 0°C. The alcohol is ethanol. The alkaline solution is sodium bicarbonate solution.

[0014] Preferably, in step (2), the sulfonating agent is 98 wt% concentrated sulfuric acid; the vacuum drying temperature is 40–90 °C.

[0015] The application of sulfonated hydrocarbon polymer electrolytes with protecting groups as described above in low-temperature proton exchange membrane fuel cells.

[0016] Furthermore, the low-temperature proton exchange membrane fuel cell includes a membrane electrode assembly, which includes a proton exchange membrane, a catalyst layer, and a diffusion layer. The proton exchange membrane is prepared from a sulfonated hydrocarbon polymer.

[0017] Furthermore, the low-temperature proton exchange membrane fuel cell includes a membrane electrode assembly, which includes a proton exchange membrane, a catalyst layer, and a diffusion layer. The catalyst layer is prepared by spraying a catalyst ink containing a sulfonated hydrocarbon polymer binder.

[0018] Furthermore, the content of the polymer binder in the catalyst layer is 5 to 30 wt% (based on the total mass of the catalyst layer), for example, the content of the polymer binder in the catalyst layer is 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, or 30 wt%.

[0019] Furthermore, the catalyst contained in the catalyst layer is a Pt / C catalyst, and the Pt content in the Pt / C catalyst is 20 to 60 wt% (e.g., 20 wt%, 40 wt%, 50 wt% or 60 wt%).

[0020] Furthermore, the loading of Pt / C catalyst in the catalyst layer is 0.10–0.50 mg·cm³. -2 (For example, 0.1 mg·cm) -2 0.15 mg·cm -2 0.2 mg·cm -2 0.25 mg·cm -2 0.3 mg·cm -2 0.35 mg·cm -2 0.4 mg·cm -2 0.45 mg·cm -2 Or 0.5 mg·cm -2 Preferably, the catalyst ink is obtained by uniformly dispersing a mixture of binder solution, Pt / C catalyst, water and isopropanol solvent by stirring and ultrasonication; preferably, the solvent of the binder solution is a mixed solution of polymer binder dissolved in water and isopropanol (water:isopropanol = 1:1-5), and the concentration of the binder solution is 1-5 wt%.

[0021] Specifically, this invention discloses a series of efficient synthetic methods for sulfonated hydrocarbon polymers with different protecting groups and different IECs. The reaction route is shown in the following formula: indigo monomer, indigo monomer with a protecting group, and biphenyl are added dropwise with trifluoroacetic acid and superacid trifluoromethanesulfonic acid under ice bath conditions to initiate a polymerization reaction below 0°C. The polymerization reaction is carried out at room temperature to obtain a series of hydrocarbon polymers with different protecting groups and different IECs. These polymers are dissolved in 98wt% concentrated sulfuric acid and reacted at 20–60°C for a period of time until dissolved. The reaction mixture is poured into distilled water to obtain a white or yellow fibrous solid. The solid is washed repeatedly with distilled water until the washing solution is neutral. The obtained solid is then vacuum dried at 40–90°C to obtain a series of sulfonated polyhydrocarbon polymers with different protecting groups and different IECs.

[0022]

[0023] Wherein, R represents different protecting groups, n and (100-n) represent polymerization ratios, and the weight-average molecular weight of the copolymer is between 5,000 and 800,000.

[0024] Furthermore, the sulfonating agent is 98wt% concentrated sulfuric acid, and the hydrocarbon polymer can dissolve in 98wt% concentrated sulfuric acid during the reaction without the need for other organic solvents. The liquid-solid content of the reaction is 5wt%, the reaction conditions are mild, the reaction temperature is 50℃, and the reaction time is 2-10h. The IEC of the hydrocarbon polymer can be controlled by the type and ratio of the protecting groups, and the yield of the sulfonated hydrocarbon polymer is over 80%.

[0025] Furthermore, the post-processing is simple: the white or yellow fibrous solid is washed repeatedly with distilled water until the wash water is neutral. Finally, it is vacuum dried at 80°C for 10 hours to obtain IEC-controlled sulfonated hydrocarbon polymers.

[0026] This invention further discloses the application of IEC-controllable sulfonated hydrocarbon polymers as proton exchange membranes in low-temperature proton exchange membrane fuel cells. Experimental results show that the preferred sulfonated hydrocarbon polymer (SPIB) is... 50 -RPIB 50 R (F, Cl, Br, NO2) is used in proton exchange membrane materials for fuel cells, exhibiting low water absorption and size swelling.

[0027] (1) At 20℃, SPIB 50 -RPIB 50 The water absorption percentage of the polymer (R = F, Cl, Br, NO2) is 26-34 wt%, which is less than that of SPIB. 100 The polymer absorbs 84 wt% of water; at 80°C, SPIB 50 -RPIB 50The water absorption of the (R=F,Cl,Br,NO2) polymer is 34-39wt%, which is much lower than that of SPIB. 100 The polymer absorbs 366 wt% of water.

[0028] (2) At 20℃, SPIB 50 -RPIB 50 The water absorption swelling ratio of the polymer (R = F, Cl, Br, NO2) is 10-11%, which is less than that of SPIB. 100 The polymer has a swelling ratio of 29%; at 80°C, SPIB 50 -RPIB 50 The water absorption swelling ratio of the (R=F,Cl,Br,NO2) polymer is 12-15%, which is much lower than that of SPIB. 100 The polymer has a swelling ratio of 78%.

[0029] This invention further discloses the application of IEC-controllable sulfonated hydrocarbon polymers as proton exchange membranes and ionomer binders in the preparation of proton exchange membrane fuel cells, exhibiting good battery performance and stability. Experimental results show that, under operating conditions of 80°C without any humidification or pressurization, this polymer, when used as a proton exchange membrane in a hydrogen-oxygen fuel cell, achieves a maximum power density of 1.00 W / cm². 2 At a current density of 0.3 A / cm² 2 Under accelerated testing conditions, the battery voltage did not decrease significantly after 90 hours. This polymer, used as a binder in a hydrogen-oxygen fuel cell, achieved a maximum power density of 0.60 W / cm³. 2 At a current density of 0.3 A / cm² 2 Under accelerated testing conditions, the battery voltage did not decrease significantly after 190 hours.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0031] (1) The polymer electrolyte of the present invention is a sulfonated hydrocarbon high molecular weight copolymer containing different protecting groups. The present invention uses biphenyl and indigo in different proportions and indigo monomers containing different protecting groups for acid-catalyzed polymerization, followed by sulfonation with concentrated sulfuric acid to obtain an IEC-controllable sulfonated polymer electrolyte. This polymer exhibits controllable water absorption capacity, good dimensional stability, mechanical stability, and oxidative stability, and shows excellent performance as a proton exchange membrane and ionomer binder in low-temperature proton exchange membrane fuel cells;

[0032] (2) The sulfonated polymer prepared by this invention has good solubility and can be dissolved in a variety of polar solvents such as DMF, NMP, DMAc, and DMSO at room temperature, and can be used to prepare proton exchange membranes; it is also easily soluble in a mixed solution of water and isopropanol and can be used to prepare ionomer solutions.

[0033] (3) The sulfonated polymer electrolyte of the present invention can meet the performance requirements of fuel cells, and has excellent power density and long-term stability. When applied to hydrogen-oxygen fuel cells, the polymer was tested and found to achieve a maximum power density of 1.00 W / cm² under conditions of 80°C and 100% relative humidity as a proton exchange membrane. 2 At 0.3A / cm 2 At a given current density, the voltage decay is close to 0.22 mV / h after 90 hours; as an ionomer binder, the maximum power density of the battery can reach 0.60 W / cm³. 2 At 0.3A / cm 2 At a current density, the voltage decay is close to 0.16 mV / h over 190 hours. Attached Figure Description

[0034] Figure 1 This is a comparison of the water absorption rate data of the sulfonated hydrocarbon polymer membranes prepared in Examples 1-4 and Comparative Example 1.

[0035] Figure 2 This is a comparison of the swelling ratio data of the sulfonated hydrocarbon polymer films prepared in Examples 1-4 and Comparative Example 1.

[0036] Figure 3 The tensile property curves of the sulfonated hydrocarbon polymer films prepared in Examples 1-4 are compared with those of Comparative Example 1. (a) Elongation at break and tensile strength in the wet state, and (b) Elongation at break and tensile strength in the dry state.

[0037] Figure 4 SPIB, the polymer of Example 1 50 -FPIB 50 Comparison of polarization curves and power density curves when used as membrane and ionomer binders respectively in low-temperature proton exchange membrane fuel cells. (a) SPIB of Example 1 50 -FPIB 50 (a) Power density, current density and voltage relationship of (membrane) / Nafion (binder); (b) Gore (membrane) / SPIB of Example 1 50 -FPIB 50 (c) Relationship between power density, current density and voltage of the adhesive; (d) SPIB of Example 1 50 -FPIB 50 (d) Voltage-time relationship of (membrane) / Nafion (binder); Gore (membrane) / SPIB in Example 1 50 -FPIB 50 (Adhesive) Voltage and time relationship graph. Detailed Implementation

[0038] To make the present invention more apparent and understandable, preferred embodiments are described in detail below with reference to the accompanying drawings.

[0039] In the following embodiments of the present invention, concentrated sulfuric acid (98 wt%) was used;

[0040] In a water / isopropanol mixed solvent, the mass ratio of water to isopropanol is 1:4;

[0041] Pt / C catalyst (50wt% Pt / C, TKK).

[0042] Example 1

[0043] SPIB, a hydrocarbon polymer containing F-atom protecting groups n -FPIB 100-n The synthesis method of (n = 50, 70, 90) and its application in H2 / O2 fuel cells includes the following steps:

[0044] (1) Polymer precursor PIB n -FPIB 100-n Composition of (n = 90, 70, 50):

[0045] At room temperature, the reactants, biphenyl (1.54 g, 10.0 mmol), were first added to indigo (0.81 g, 5.5 mmol), and 5-fluoroindigo monomer (0.91 g, 5.5 mmol) were added to a three-necked flask. Then, dichloromethane (2 mL) was added and stirred until homogeneous. Trifluoroacetic acid (TFA) (2.0 mL) was then added and stirred until homogeneous. Under ice bath conditions (reaction system temperature below 0°C), trifluoromethanesulfonic acid (TFSA) (8.0 mL) was added dropwise to initiate the polymerization reaction. The system was then gradually heated to room temperature. After 4 hours of reaction, the viscosity of the system increased. The mixture was then slowly poured into ethanol to obtain a fibrous polymer. Excess acid in the solution was removed with 0.50 mol / L sodium bicarbonate solution, followed by repeated washing with deionized water until the system was neutral. The mixture was then filtered to obtain a fibrous solid polymer, which is the polymer precursor PIB containing the F protecting group. 50 -FPIB 50 The ratio of the two monomers was changed to indigo (1.13 g, 7.7 mmol) and 5-fluoroindigo monomer (0.54 g, 3.3 mmol), while the remaining experimental procedures remained the same, to obtain the polymer precursor PIB. 70 -FPIB 30 Similarly, by changing the ratio of the two monomers to indigo (1.46 g, 9.9 mmol) and 5-fluoroindigo monomer (0.18 g, 1.1 mmol), and keeping the other experimental procedures the same, the polymer precursor PIB was obtained. 90 -FPIB 10 .

[0046]

[0047] (2) Sulfonated polymer SPIB n -FPIB 100-n Composition of (n = 90, 70, 50):

[0048] PIB n -FPIB 100-n (n = 90, 70, 50) (2g) was added to a three-necked flask, and concentrated sulfuric acid (98wt%) (40mL) was added as the sulfonating reagent. The solid-liquid content of the reaction solution was 5wt%, and the reaction temperature was 50℃. The reaction was carried out for 4 hours until the polymer dissolved in the concentrated sulfuric acid (98wt%). The solution was then precipitated into distilled water to obtain a white flocculent substance. The substance was washed several times with distilled water until the system was neutral. The filtered polymer was then vacuum dried at 80℃ for 10 hours to obtain the sulfonated polymer SPIB. n -FPIB 100-n (n = 90, 70, 50).

[0049]

[0050] (3) SPIB 50 -FPIB 50 Applications of proton exchange membranes in H2 / O2 fuel cells:

[0051] The polymer SPIB prepared in step (2) above 50 -FPIB 50 A 6 wt% solution was prepared by dissolving the solvent in dimethyl sulfoxide (DMSO). After filtration to remove air bubbles, the solution was poured onto a clean glass plate and dried at 80°C and atmospheric pressure for 12 hours. Then, it was dried in distilled water at 50°C for 24 hours to completely remove residual solvent. The resulting sulfonated proton exchange membrane (15–25 μm thick) was obtained. A prepared catalyst slurry (composed of 50 wt% Pt / C catalyst (TKK), water, isopropanol, and 5% Nafion solution; where the mass ratio of 50 wt% Pt / C catalyst (TKK): Nafion: water = 4:1:20, and the mass ratio of water: isopropanol = 1:4) was sprayed onto both sides of the proton exchange membrane (Pt content 0.35 mg / cm³). 2 The fuel cell is loaded into the fuel cell test fixture and connected to the fuel cell test system for testing. Test conditions: Under conditions of no back pressure and 100% relative humidity, the flow rates of H2 and O2 are simultaneously set to 200 and 500 sccm, respectively, and the fuel cell performance (maximum power density and stability under constant current density) is tested at 80°C.

[0052] (4)SPIB 50 -FPIB50 Application of ionomer binders in H2 / O2 fuel cells:

[0053] The SPIB containing an F protecting group prepared above. 50 -FPIB 50 A polymer binder was dissolved in a water / isopropanol mixture (water to isopropanol mass ratio = 1:4) to prepare an ionomer solution. The ionomer solution and a Pt / C catalyst (50wt% Pt / C, TKK) were dispersed in the water / isopropanol mixture. After homogenization by magnetic stirring and ultrasonic mixing, a catalyst slurry (50wt% Pt / C(TKK) catalyst: ionomer: water = 8:2:20, water:isopropanol mass ratio = 1:4) was obtained. This catalyst slurry was then sprayed onto both sides of a proton exchange membrane (Gore M 820.15) (Pt content 0.35 mg / cm² on each side). 2 The proton exchange membrane was sandwiched between two sides using carbon paper (Sigracet 22BB, SGL Carbon), and then placed in a fuel cell test fixture and connected to a fuel cell test system for testing. Test conditions: Under conditions of no back pressure and 100% relative humidity, the flow rates of H2 and O2 were simultaneously set to 200 and 500 sccm, respectively, and the fuel cell performance (maximum power density and stability under constant current density) was tested at 80°C.

[0054] Example 2

[0055] SPIB, a hydrocarbon polymer containing Cl atom protecting groups n -ClPIB 100-n The synthesis method of (n = 50, 70, 90) and its application in H2 / O2 fuel cells includes the following steps:

[0056] (1) At room temperature, the reactant biphenyl (1.54 g, 10.0 mmol) was first added to indigo (0.81 g, 5.5 mmol), and 5-chloroindigo monomer (1.00 g, 5.5 mmol) was added to a three-necked flask. Then, dichloromethane (2 mL) was added as solvent and stirred until homogeneous. Trifluoroacetic acid (TFA) (2.0 mL) was then added and stirred until homogeneous. Under ice bath conditions (reaction system temperature below 0 °C), trifluoromethanesulfonic acid (TFSA) (8.0 mL) was added dropwise to the solution to initiate the polymerization reaction. The system was then gradually heated to room temperature. After 3 hours of reaction, the viscosity of the system increased, and post-treatment was performed. The remaining experimental steps were the same as in Example 1, step (1).

[0057] The ratio of the two monomers was changed to indigo (1.13 g, 7.7 mmol) and 5-chloroindigo monomer (0.60 g, 3.3 mmol), while the remaining experimental procedures remained the same, to obtain the polymer precursor PIB.70 -ClPIB 30 Similarly, by changing the ratio of the two monomers to indigo (1.46 g, 9.9 mmol) and 5-chloroindigo monomer (0.20 g, 1.1 mmol), and keeping the other experimental procedures the same, the polymer precursor PIB was obtained. 90 -ClPIB 10 .

[0058]

[0059] (2) Sulfonated polymer SPIB n -ClPIB 100-n Composition of (n = 90, 70, 50):

[0060] PIB n -ClPIB 100-n (n = 90, 70, 50) (2g) was added to a three-necked flask, and concentrated sulfuric acid (40mL) was added as the sulfonation reagent. The solid content of the reaction liquid was 5wt%, and the reaction temperature was 50℃. The reaction was carried out for 4h until the polymer dissolved in the concentrated sulfuric acid. The solution was then precipitated into distilled water to obtain a white flocculent substance. The substance was washed several times with distilled water until the system was neutral. The filtered polymer was then vacuum dried at 80℃ for 10h to obtain the sulfonated polymer SPIB. n -ClPIB 100-n (n = 90, 70, 50).

[0061]

[0062] The remaining application steps are the same as in Example 1.

[0063] Example 3

[0064] SPIB, a hydrocarbon polymer containing Br-atom protecting groups n -BrPIB 100-n The synthesis method of (n = 50, 70, 90) and its application in H2 / O2 fuel cells includes the following steps:

[0065] (1) At room temperature, the reactants biphenyl (1.54 g, 10.0 mmol) were first added to indigo (0.81 g, 5.5 mmol), and 5-bromoindigo monomer (1.24 g, 5.5 mmol) were added to a three-necked flask. Then, dichloromethane (2 mL) was added as solvent and stirred until homogeneous. Trifluoroacetic acid (TFA) (2.0 mL) was then added and stirred until homogeneous. Under ice bath conditions (reaction system temperature below 0 °C), trifluoromethanesulfonic acid (TFSA) (8.0 mL) was added dropwise to the solution to initiate the polymerization reaction. The system was then gradually heated to room temperature. After 3 hours of reaction, the viscosity of the system increased, and post-treatment was performed. The remaining experimental steps were the same as in Example 1, step (1).

[0066] The ratio of the two monomers was changed to indigo (1.13 g, 7.7 mmol) and 5-bromoindomethacin monomer (0.75 g, 3.3 mmol), while the remaining experimental procedures remained the same, to obtain the polymer precursor PIB. 70 -BrPIB 30 Similarly, by changing the ratio of the two monomers to indigo (1.46 g, 9.9 mmol) and 5-bromoindigo monomer (0.25 g, 1.1 mmol), and keeping the other experimental procedures the same, the polymer precursor PIB was obtained. 90 -BrPIB 10 .

[0067]

[0068] (2) Sulfonated polymer SPIB n -BrPIB 100-n Composition of (n = 90, 70, 50):

[0069] PIB n -BrPIB 100-n (n = 90, 70, 50) (2g) was added to a three-necked flask, and concentrated sulfuric acid (40mL) was added as the sulfonation reagent. The solid content of the reaction liquid was 5wt%, and the reaction temperature was 50℃. The reaction was carried out for 4h until the polymer dissolved in the concentrated sulfuric acid. The solution was then precipitated into distilled water to obtain a white flocculent substance. The substance was washed several times with distilled water until the system was neutral. The filtered polymer was then vacuum dried at 80℃ for 10h to obtain the sulfonated polymer SPIB. n -BrPIB 100-n (n = 90, 70, 50).

[0070]

[0071] The remaining application steps are the same as in Example 1.

[0072] Example 4

[0073] SPIB, a hydrocarbon polymer containing NO2 protecting groups n -NO2PIB 100-n The synthesis method of (n = 50, 70, 90) and its application in H2 / O2 fuel cells includes the following steps:

[0074] (1) At room temperature, the reactant biphenyl (1.54 g, 10.0 mmol) was first added to indigo (0.81 g, 5.5 mmol), and 5-nitroindoin monomer (1.06 g, 5.5 mmol) was added to a three-necked flask. Then, dichloromethane (2 mL) was added as solvent and stirred until homogeneous. Trifluoroacetic acid (TFA) (2.0 mL) was then added and stirred until homogeneous. Under ice bath conditions (reaction system temperature below 0 °C), trifluoromethanesulfonic acid (TFSA) (8.0 mL) was added dropwise to the solution to initiate the polymerization reaction. The system was then gradually heated to room temperature. After 3 hours of reaction, the viscosity of the system increased, and post-treatment was performed. The remaining experimental steps were the same as in Example 1, step (1).

[0075] The ratio of the two monomers was changed to indigo (1.13 g, 7.7 mmol) and 5-nitroindoin monomer (0.63 g, 3.3 mmol), while the remaining experimental procedures were the same, to obtain the polymer precursor PIB. 70 -NO2PIB 30 Similarly, by changing the ratio of the two monomers to indigo (1.46 g, 9.9 mmol) and 5-nitroindigo monomer (0.21 g, 1.1 mmol), and keeping the other experimental procedures the same, the polymer precursor PIB was obtained. 90 -NO2PIB 10 .

[0076]

[0077] (2) Sulfonated polymer SPIB n -NO2PIB 100-n Composition of (n = 90, 70, 50):

[0078] PIB n -NO2PIB 100-n (n = 90, 70, 50) (2g) was added to a three-necked flask, and concentrated sulfuric acid (40mL) was added as the sulfonation reagent. The solid content of the reaction liquid was 5wt%, and the reaction temperature was 50℃. The reaction was carried out for 4h until the polymer dissolved in the concentrated sulfuric acid. The solution was then precipitated into distilled water to obtain a yellow flocculent substance. The substance was washed several times with distilled water until the system was neutral. The filtered polymer was then vacuum dried at 80℃ for 10h to obtain the sulfonated polymer SPIB. n -NO2PIB 100-n (n = 90, 70, 50).

[0079]

[0080] The remaining application steps are the same as in Example 1.

[0081] Example 5

[0082] SPIB, a hydrocarbon polymer containing an I-atom protecting groupn -IPIB 100-n The synthesis method of (n = 50, 70, 90) and its application in H2 / O2 fuel cells includes the following steps:

[0083] (1) At room temperature, the reactant biphenyl (1.54 g, 10.0 mmol) was first added to indigo (0.81 g, 5.5 mmol), and 5-iodoindigo monomer (1.64 g, 6.0 mmol) was added to a three-necked flask. Then, dichloromethane (2 mL) was added as solvent and stirred until homogeneous. Trifluoroacetic acid (TFA) (2.0 mL) was then added and stirred until homogeneous. Under ice bath conditions (reaction system temperature below 0 °C), trifluoromethanesulfonic acid (TFSA) (8.0 mL) was added dropwise to the solution to initiate the polymerization reaction. The system was then gradually heated to room temperature. After 3 hours of reaction, the viscosity of the system increased, and post-treatment was performed. The remaining experimental steps were the same as in Example 1, step (1).

[0084] The ratio of the two monomers was changed to indigo (1.13 g, 7.7 mmol) and 5-iodoindomethacin monomer (0.98 g, 3.6 mmol), while the remaining experimental procedures remained the same, to obtain the polymer precursor PIB. 70 -IPIB 30 Similarly, by changing the ratio of the two monomers to indigo (1.46 g, 9.9 mmol) and 5-iodoindomethacin monomer (0.33 g, 1.2 mmol), and keeping the other experimental procedures the same, the polymer precursor PIB was obtained. 90 -IPIB 10 .

[0085]

[0086] (2) Sulfonated polymer SPIB n -IPIB 100-n Composition of (n = 90, 70, 50):

[0087] PIB n -IPIB 100-n (n = 90, 70, 50) (2g) was added to a three-necked flask, and concentrated sulfuric acid (40mL) was added as the sulfonation reagent. The solid content of the reaction liquid was 5wt%, and the reaction temperature was 50℃. The reaction was carried out for 6 hours until the polymer dissolved in the concentrated sulfuric acid. The solution was then precipitated into distilled water to obtain a white flocculent substance. The substance was washed several times with distilled water until the system was neutral. The filtered polymer was then vacuum dried at 80℃ to obtain the sulfonated polymer SPIB. n -IPIB 100-n (n = 90, 70, 50).

[0088]

[0089] The remaining application steps are the same as in Example 1.

[0090] Example 6

[0091] SPIB, a hydrocarbon polymer containing a -CH3 protecting group n -CH3PIB 100-n The synthesis method of (n = 50, 70, 90) and its application in H2 / O2 fuel cells includes the following steps:

[0092] (1) At room temperature, firstly, add 1.54 g (10.0 mmol) of biphenyl (indigo) to a three-necked flask, then add 0.81 g (5.5 mmol) of indigo and 1.06 g (5.5 mmol) of 5-methylindigo monomer to the flask. Next, add 2 mL of dichloromethane solvent and stir until homogeneous. Then, add 2.0 mL of trifluoroacetic acid (TFA) and stir until homogeneous. Under ice bath conditions (reaction system temperature below 0°C), add 8.0 mL of trifluoromethanesulfonic acid (TFSA) dropwise to the solution to initiate the polymerization reaction. Then, gradually raise the system temperature to room temperature. After reacting for 3 hours, the viscosity of the system increases, and post-treatment is performed. The remaining experimental steps are the same as in Example 1, step (1).

[0093] The ratio of the two monomers was changed to indigo (1.13 g, 7.7 mmol) and 5-methylindigo monomer (0.63 g, 3.3 mmol), while the remaining experimental procedures were the same, to obtain the polymer precursor PIB. 70 -CH3PIB 30 Similarly, by changing the ratio of the two monomers to indigo (1.46 g, 9.9 mmol) and 5-methylindigo monomer (0.21 g, 1.1 mmol), and keeping the other experimental procedures the same, the polymer precursor PIB was obtained. 90 -CH3PIB 10 .

[0094]

[0095] (2) Sulfonated polymer SPIB n -CH3PIB 100-n Composition of (n = 90, 70, 50):

[0096] PIB n -CH3PIB 100-n (n = 90, 70, 50) (2g) was added to a three-necked flask, and concentrated sulfuric acid (40mL) was added as the sulfonation reagent. The solid content of the reaction liquid was 5wt%, and the reaction temperature was 50℃. The reaction was carried out for 3 hours until the polymer dissolved in the concentrated sulfuric acid. The solution was then precipitated into distilled water to obtain a yellow flocculent substance. The substance was washed several times with distilled water until the system was neutral. The filtered polymer was then vacuum dried at 80℃ to obtain the sulfonated polymer SPIB. n -CH3PIB 100-n(n = 90, 70, 50).

[0097]

[0098] The remaining application steps are the same as in Example 1.

[0099] Example 7

[0100] SPIB, a hydrocarbon polymer containing a -CH3O protecting group n -CH3OPIB 100-n The synthesis method of (n = 50, 70, 90) and its application in H2 / O2 fuel cells includes the following steps:

[0101] (1) At room temperature, firstly, add 1.54 g (10.0 mmol) of biphenyl (indigo) to a three-necked flask, then add 0.81 g (5.5 mmol) of indigo and 1.06 g (5.5 mmol) of 5-methoxyindigo monomer to the flask. Next, add 2 mL of dichloromethane solvent and stir until homogeneous. Then, add 2.0 mL of trifluoroacetic acid (TFA) and stir until homogeneous. Under ice bath conditions (reaction system temperature below 0°C), add 8.0 mL of trifluoromethanesulfonic acid (TFSA) dropwise to the solution to initiate the polymerization reaction. Then, gradually raise the system temperature to room temperature. After reacting for 3 hours, the viscosity of the system increases, and post-treatment is performed. The remaining experimental steps are the same as in Example 1, step (1).

[0102] The ratio of the two monomers was changed to indigo (1.13 g, 7.7 mmol) and 5-methoxyindigo monomer (0.63 g, 3.3 mmol), while the remaining experimental procedures remained the same, to obtain the polymer precursor PIB. 70 -CH3OPIB 30 Similarly, by changing the ratio of the two monomers to indigo (1.46 g, 9.9 mmol) and 5-methoxyindigo monomer (0.21 g, 1.1 mmol), and keeping the other experimental steps the same, the polymer precursor PIB was obtained. 90 -CH3OPIB 10 .

[0103]

[0104] (2) Sulfonated polymer SPIB n -CH3OPIB 100-n Composition of (n = 90, 70, 50):

[0105] PIB n -CH3OPIB 100-n(n = 90, 70, 50) (2g) was added to a three-necked flask, and concentrated sulfuric acid (40mL) was added as the sulfonation reagent. The solid content of the reaction liquid was 5wt%, and the reaction temperature was 50℃. The reaction was carried out for 10h until the polymer dissolved in the concentrated sulfuric acid. The solution was then precipitated into distilled water to obtain a white flocculent substance. The substance was washed several times with distilled water until the system was neutral. The filtered polymer was then vacuum dried at 80℃ to obtain the sulfonated polymer SPIB. n -CH3OPIB 100-n (n = 90, 70, 50).

[0106]

[0107] The remaining application steps are the same as in Example 1.

[0108] Comparative Example 1

[0109] SPIB, a hydrocarbon polymer without protecting groups 100 The synthesis method of [the substance] and its application in H2 / O2 fuel cells include the following steps:

[0110] (1) At room temperature, firstly, add 1.54 g (10.0 mmol) of biphenyl (indigo) and 1.62 g (11 mmol) of indigo to a three-necked flask, then add 2 mL of dichloromethane solvent and stir until homogeneous. Next, add 2.0 mL of trifluoroacetic acid (TFA) and stir until homogeneous. Under ice bath conditions (reaction system temperature below 0°C), add 8.0 mL of trifluoromethanesulfonic acid (TFSA) dropwise to the solution to initiate the polymerization reaction. Then, gradually raise the system temperature to room temperature. After reacting for 4 hours, the viscosity of the system increases, and post-treatment is performed. The remaining experimental steps are the same as in Example 1, step (1).

[0111]

[0112] (2) Sulfonated polymer SPIB 100 Synthesis:

[0113] PIB 100 Add 2g of the polymer to a three-necked flask, add 40mL of concentrated sulfuric acid as the sulfonation reagent, the solid content of the reaction liquid is 5wt%, the reaction temperature is 50℃, and the reaction is carried out for 4h until the polymer dissolves in the concentrated sulfuric acid. The solution is then precipitated into distilled water to obtain a white flocculent substance, which is washed several times with distilled water until the system is neutral. The filtered polymer is then vacuum dried at 80℃ for 10h to obtain the sulfonated polymer SPIB. 100 .

[0114]

[0115] The remaining application steps are the same as in Example 1.

[0116] Performance test results:

[0117] Depend on Figure 1 This demonstrates that by changing the type and number of protecting groups, the IEC of the polymer can be effectively controlled, thereby regulating the water absorption capacity of the sulfonated proton exchange membranes (hereinafter referred to as polymer membranes) prepared in each example and comparative example. At 80°C, the SPIB in Examples 1-4 showed a significant change. 50 -RPIB 50 The water absorption rate of the (R=F,Cl,Br,NO2) polymer is 34-39wt%, SPIB 70 -RPIB 30 The water absorption rate of the (R=F,Cl,Br,NO2) polymer is 53-72wt%, SPIB 90 -RPIB 10 The water absorption rate of the (R=F,Cl,Br,NO2) polymer is 101-165wt%, which is much lower than that of SPIB in Comparative Example 1. 100 The polymer had a water absorption rate of 366 wt%. The results indicate that the introduction of protecting groups such as F, Cl, Br, and NO2 at the R3 position effectively controlled the polymer's water absorption rate; and as the degree of sulfonation decreased, the polymer's IEC value decreased, and the water absorption rate decreased as well.

[0118] Figure 2 This demonstrates that by changing the type and number of protecting groups, the IEC of the polymer was effectively controlled, thus effectively controlling the swelling ratio of the polymer film (swelling ratio = the difference between the length of the polymer film in water at 80°C and the length of the polymer film after drying ÷ the length of the polymer film after drying). SPIB in Examples 1-4 showed significant changes at 80°C. 50 -RPIB 50 The swelling ratio of the polymer (R=F,Cl,Br,NO2) is 12-15%, SPIB 70 -RPIB 30 The swelling ratio of the polymer (R=F,Cl,Br,NO2) is 17-21%, SPIB 90 -RPIB 10 The swelling ratio of the polymer (R = F, Cl, Br, NO2) is 30-44%, which is much lower than that of SPIB in Comparative Example 1. 100 The polymer swelling ratio was 78%. The results indicate that the introduction of protecting groups such as F, Cl, Br, and NO2 at the R3 position effectively controls the polymer swelling ratio; and as the degree of sulfonation decreases, the polymer IEC value decreases, and the swelling ratio decreases.

[0119] Figure 3 The SPIBs prepared in each embodiment showed improved performance after reducing IEC. 50 -RPIB 50Sulfonated proton exchange membranes (referred to as polymer membranes) exhibit reduced water absorption and improved mechanical properties under both dry and wet conditions. The polymer membrane (length × width = 4 cm × 1.5 cm) was tested using a CMT-4502 (MTS SYSTEMS CO.,LTD) thin film tensile properties test method (GB / T 13022-1991) at a tensile speed of 2 mm / min. (a) shows the tensile strength and elongation at break in the wet state, and (b) shows the tensile strength and elongation at break in the dry state. Here, the wet performance was obtained by directly testing the polymer membrane after removing it from ultrapure water and wiping off the surface water; the dry performance was obtained by vacuum drying the polymer membrane after removing it from the water. Under wet conditions, compared to SPIB in Comparative Example 1... 100 The tensile strength of the polymer film was 15 MPa. In Examples 1-4, the IEC decreased significantly after SPIB treatment. 50 -RPIB 50 The tensile strength of the polymer film (R = F, Cl, Br, NO2) increased to 28-45 MPa. Under dry conditions, compared to SPIB in Comparative Example 1, this represents a significant improvement. 100 The tensile strength of the polymer film is 57 MPa, and the SPIB after the IEC reduction in Examples 1-4 is... 50 -RPIB 50 The tensile strength of the (R=F,Cl,Br,NO2) polymer film increases to 80-84MPa.

[0120] Figure 4 SPIB polymers exhibit control over water absorption 50 -FPIB 50 As a membrane and binder, it exhibited good stability in battery testing; the sulfonated polymer in Example 1, used as a proton exchange membrane or binder in a hydrogen-oxygen fuel cell, achieved a maximum power density of 1.00 W / cm² when the H₂ / O₂ gas flow rate was 500 sccm. 2 (Current density 2.63 A / cm) 2 ), 0.60W / cm 2 (Current density 1.73 A / cm) 2 Under accelerated testing conditions (current density of 0.3 A / cm²), 2 Under these conditions, the battery voltage showed no significant decrease after 90 hours (decaying from 0.67V to 0.65V) and 190 hours (decaying from 0.63V to 0.60V), respectively, demonstrating high stability. (a) SPIB of Example 1 50 -FPIB 50 (a) Power density, current density and voltage relationship of (membrane) / Nafion (binder); (b) Gore (membrane) / SPIB of Example 1 50 -FPIB 50(c) Relationship between power density, current density and voltage of the adhesive; (d) SPIB of Example 1 50 -FPIB 50 (d) Voltage-time relationship of (membrane) / Nafion (binder); Gore (membrane) / SPIB in Example 1 50 -FPIB 50 (Adhesive) Voltage and time relationship graph.

[0121] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention in any form or substance. It should be noted that those skilled in the art can make several improvements and additions without departing from the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention.

Claims

1. A sulfonated hydrocarbon polymer containing a protecting group, characterized in that, A copolymer comprising the following repeating structural units: or ; Wherein, R3 is selected from F, Cl, Br, NO2, CH3 or CH3O, R1, R2 and R4 are each independently selected from H, F, Cl, Br, NO2 or CH3, n and (100-n) represent the polymerization ratio, n is selected from an integer from 20 to 98, and the weight average molecular weight of the polymer is between 5000 and 800000.

2. The sulfonated hydrocarbon polymer containing a protecting group according to claim 1, characterized in that, When R3 is selected from F, Cl, Br, NO2, CH3 or CH3O, R1 is H, R2 is H, and R4 is H.

3. The sulfonated hydrocarbon polymer containing a protecting group according to claim 1, characterized in that, n = 50, 70, or 90.

4. The method for synthesizing the sulfonated hydrocarbon polymer according to claim 1, characterized in that, Includes the following steps: (1) At room temperature, the reaction raw materials indigo, indigo monomer with protecting group, biphenyl, polar organic solvent and trifluoroacetic acid are first mixed and stirred until uniform; under ice bath conditions, trifluoromethanesulfonic acid is added dropwise to the solution to initiate the polymerization reaction, and then the system is gradually heated to room temperature. The mixture is then poured into alcohol to obtain fibrous polymer. Excess acid in the solution is removed with alkaline solution, and then the system is washed multiple times with deionized water until neutral. The fibrous solid polymer is then filtered to obtain the polymer precursor with protecting group. (2) The polymer precursor and sulfonating agent are mixed to obtain a reaction solution with a solid content of 3-6 wt% and a reaction temperature of 20-60℃. The reaction is continued until the polymer dissolves in the sulfonating agent. The solution is then immersed in distilled water to obtain flocculent material. The flocculent material is washed several times with distilled water until the system is neutral. The sulfonated polymer obtained by filtration is then vacuum dried to obtain a sulfonated polymer with low ion exchange capacity.

5. The method according to claim 4, characterized in that, In step (1), the indigo monomer containing the protecting group is 5-fluoroindigo, 5-chloroindigo, 5-bromoindigo or 5-nitroindigo.

6. The method according to claim 4, characterized in that, In step (1), the molar ratio of biphenyl: indigo: indigo monomer with protecting group is 10: (2~11): (0.5~9).

7. The method according to claim 4, characterized in that, In step (1), the ratio of biphenyl, polar organic solvent, trifluoroacetic acid and trifluoromethanesulfonic acid is 10 mol: 1~4 mL: 1~4 mL: 5~10 mL.

8. The method according to claim 4, characterized in that, In step (1), the polar solvent is dichloromethane at room temperature; the reaction system temperature is below 0 °C under ice bath conditions; the alcohol is ethanol; and the alkaline solution is sodium bicarbonate solution.

9. The method according to claim 4, characterized in that, In step (2), the sulfonating agent is 98 wt% concentrated sulfuric acid; the vacuum drying temperature is 40~90℃.

10. The application of the sulfonated hydrocarbon polymer containing a protecting group as described in claim 1 in a low-temperature proton exchange membrane fuel cell.

11. The application as described in claim 10, characterized in that, The low-temperature proton exchange membrane fuel cell includes a membrane electrode assembly, which includes a proton exchange membrane, a catalyst layer, and a diffusion layer. The proton exchange membrane is made of sulfonated hydrocarbon polymers.

12. The application as described in claim 10, characterized in that, The low-temperature proton exchange membrane fuel cell includes a membrane electrode assembly, which includes a proton exchange membrane, a catalyst layer, and a diffusion layer. The catalyst layer is prepared by spraying a catalyst ink containing a sulfonated hydrocarbon polymer binder. The catalyst ink is obtained by stirring and ultrasonically dispersing a mixture of binder solution, Pt / C catalyst, water, and isopropanol solvent.

13. The application as described in claim 12, characterized in that, The solvent of the adhesive solution is a mixed solution of polymer adhesive dissolved in water and isopropanol, and the concentration of the adhesive solution is 1~5 wt%.

14. The application as described in claim 11, characterized in that, The content of polymer binder in the catalyst layer is 5~30wt%.

15. The application as described in claim 11, characterized in that, The catalyst contained in the catalyst layer is a Pt / C catalyst, and the Pt content in the Pt / C catalyst is 20~60 wt%.

16. The application as described in claim 11, characterized in that, The loading of Pt / C catalyst in the catalyst layer is 0.10~0.50 mg·cm³. -2 .